Marriage Registration in Islamic Law: A Perspective on Administrative Responsibility and Family Protection - Muhammadong Muhammadong (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
In Islamic law, marriage registration is very significant for both legal and religious reasons. It is a crucial part of making sure that both the administrative duties of marriage and the safety of the family are protected. In Islamic law, marriage is not just a social contract but also a religious duty that necessitates adequate documentation to safeguard the rights of both parties involved. This paper seeks to investigate the notion of marriage registration through the lens of Islamic law, analyzing its function in protecting familial rights, providing legal safeguards, and performing administrative responsibilities. The study methodology utilized is a qualitative approach, incorporating a literature review and document analysis of Islamic legal texts and pertinent current legal systems. The results show that registering a marriage in Islamic law is important not just for making the marriage official, but also for getting legal recognition, avoiding conflicts, and making sure that family members, especially women and children, are safe under the law. The registration process also makes it clear what the marriage's legal status is and what it means for things like inheritance, custody, and other family issues. In conclusion, marriage registration is an important part of Islamic law that upholds justice, protects the family, and makes sure that the marriage is legally protected and accountable.